2003
DOI: 10.1021/jp0301296
|View full text |Cite
|
Sign up to set email alerts
|

Bound and Quasibound States of He2H+ and He2D+

Abstract: Bound and quasibound states of He 2 H + and He 2 D + in three dimensions have been computed by use of a time-dependent quantum-mechanical wave packet approach for total angular momentum J ) 0. Seven bound states were found for He 2 H + and 14 for He 2 D + , as compared to five for both systems by Lee and Secrest (J. Chem. Phys. 1986, 85, 6565). The potential energy surface needed for the dynamical calculation has been computed by carrying out an ab initio calculation with coupled cluster single and double exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 28 publications
5
27
0
Order By: Relevance
“…Also, previous works have shown that the vibro-rotational energy levels supported by the [He-H-He] + PES do not correspond to any particular mode but to a combination of them. 87 Focusing on the comparison with previous works using ENMO approaches, it can be noticed that our value for R X−He is quite close to that obtained in Ref. 61 using the APMO-MP2 method (see Table IV).…”
Section: B [He-h-he] + and Its Isotopomerssupporting
confidence: 87%
“…Also, previous works have shown that the vibro-rotational energy levels supported by the [He-H-He] + PES do not correspond to any particular mode but to a combination of them. 87 Focusing on the comparison with previous works using ENMO approaches, it can be noticed that our value for R X−He is quite close to that obtained in Ref. 61 using the APMO-MP2 method (see Table IV).…”
Section: B [He-h-he] + and Its Isotopomerssupporting
confidence: 87%
“…Therefore, for comparison purposes we set as reference the HeH bond distance of 1.75 a.u. calculated with CCSD(T) 1. We note that the conventional electronic structure geometries differ by only ±0.01 a.u.…”
Section: Resultsmentioning
confidence: 89%
“…Although noble gas dimers Rg 2 (Rg = He, Ne, Ar) are barely stable, with binding energy of the order of a few meV, theoretical studies have shown that the inclusion of charged species such as a proton H + results in the stabilization of the dimers 1. These complexes have attracted much attention because they not only have binding energies between hydrogen and van der Waals bonds but also are good examples of symmetric “hydrogen” bonds (the proton is centrosymmetric with respect to the heavier atoms).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations